Nigella sativa oil protects against cadmium-induced intestinal toxicity via promotion of anti-inflammatory mechanisms, mucin expression and microbiota integrity (2021)
Objective: This study examined the protective effects of Nigella sativa oil (NSO) on cadmium (Cd)-induced alterations affecting gut morphology and microbiota composition, as well as the involvement of mucus glycoprotein (MUC2) and immune-inflammatory markers (TNFα and IL-2) in the colon of rats. Materials and Methods: Male Wistar rats, randomized into four groups, were treated either with distilled water (control), CdCl2 (100 mg/kg), CdCl2+NSO (1 ml/kg) or NSO alone. After the experiments, faecal samples were processed for microbial culture on various selective media, while intestinal segments were prepared for histopathological examination and immunohistochemistry. The composition of NSO was analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). Results: Oral Cd administration provoked dramatic increases in faecal counts of potentially pathogenic bacteria (Staphylococci, Enterococci, Pseudomonas and Escherichia coli), while decreasing probiotic lactobacilli counts. Cadmium treatment caused down-regulation of colonic MUC2 (p=0.003) and IL-2 (p=0.03), but increased TNFα (p=0.034), along with reduced goblet cell counts and mucus production. Conversely, treatment with NSO significantly improved Lactobacilli counts (p=0.042), while reducing the levels of potentially pathogenic species. In addition, NSO significantly restored colonic expressions of MUC2 (p=0.001), TNFα (p=0.007) and IL-2 (p=0.025) to control levels. GC-MS analysis of NSO revealed the presence of the active ingredient, thymoquinone and a high content of unsaturated fatty acids, including trans-13-octadecenoic acid and oleic acid. Conclusion: This study highlights the intestinal mucus, microbiota and immuno-inflammatory system as important protective targets of NSO against Cd-induced intestinal toxicity.